Is it not time for international guidelines to combat congenital cytomegalovirus infection? A review of central nervous system manifestations. Issue 8 (August 2020) - Gaur, P.; ffrench-Constant, S.; Kachramanoglou, C.; Lyall, H.; Jan, W.
Abstract : Cytomegalovirus (CMV) is the most commonly transmitted virus in utero with a prevalence of up to 1.5%. The infection has potentially debilitating and devastating consequences for the infected fetus, being a leading cause for neurological disability worldwide. Once acquired, it often goes undetected with only an assumed 10% of infected neonates displaying the classic clinical or imaging features. Viral DNA polymerase chain reaction (PCR) of saliva or urine obtained within the first 21 days of life is required to make the diagnosis. As the majority of infected neonates are initially asymptomatic, diagnosis is often delayed. An abnormal routine neonatal hearing test and characteristic antenatal cranial ultrasound imaging findings may raise the suspicion of congenital CMV (cCMV) in the asymptomatic group. Ultimately, the aim is to facilitate early diagnosis and timely treatment. In this article, we highlight diagnostic and treatment challenges of the commonest congenital infection, we present the current available central nervous system imaging severity grading systems, and highlight the need for an internationally agreed diagnostic grading system that can aid treatment decision-making.